Ortho-surgical Management of Severe Skeletal Class II Div 2 Malocclusion in Adult - Daokar, Suchita Tarvade; Agrawal, Gauri; Chaudhari, Charushila; Yamyar, Sheetal (Orthodontic Journal of Nepal, 2017)
Skeletal Class II malocclusion is attributed to maxillary prognathism, mandibular retrognathism or combination of both. In adolescent cases, the treatment includes growth modulation with headgear or myofunctional appliances. However in adults, optimum esthetic and functional efficacy can be achieved by orthodontic-surgical combination. This case report describes a 21 years old post-pubertal male with severe skeletal Class II discrepancy with normal maxilla and retrognathic mandible. The case was treated with bilateral sagittal split osteotomy (BSSO) with mandibular advancement approach. Straight profile, pleasing esthetics, bilateral Class I molar and canine relationship, normal overjet and overbite were achieved because of a combined ortho-surgical approach.